UNLOCKING THE POWER OF SPEECH: STRATEGIES FOR ENHANCING STUDENTS’ SPEAKING SKILLS - Baxtiyorova Lola Otabekovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation. This comprehensive guide outlines ten key strategies for enhancing students' speaking skills. It emphasizes the importance of consistent practice, active listening, and vocabulary enrichment to lay the foundation for articulate and confident communication. The incorporation of group dynamics, public speaking opportunities, and role-playing in real-life scenarios provides students with varied and practical experiences, fostering situational fluency. The inclusion of constructive feedback, language games, storytelling, and cultural exchange discussions further enriches the learning journey, making it not only educational but also engaging and culturally diverse. Overall, this annotation underscores the multifaceted approach educators can adopt to empower students in becoming effective and expressive communicators.